Graph structures for knowledge representation and reasoning : 4th International Workshop, GKR 2015, Buenos Aires, Argentina, July 25, 2015, revised selected papers /: 4th International Workshop, GKR 2015, Buenos Aires, Argentina, July 25, 2015, revised selected papers. (2015) - Unknown
No abstract available